An Overview: Laser-Based Additive Manufacturing for High Temperature Tribology - Ur Rahman, Naveed; Matthews, David Thomas Allan; de Rooij, Matthijn; Khorasani, Amir Mahyar; Gibson, Ian; Cordova, Laura; Römer, Gert-willem (Frontiers in Mechanical Engineering, 2019)
Laser-based additive manufacturing (LBAM) is a versatile manufacturing technique, extensively adopted to fabricate metallic components of enhanced properties. The current review paper provides a critical assessment of the fabricated metallic coatings and parts through LBAM-processes [e.g., laser metal deposition (LMD) and selective laser melting (SLM)] for high temperature tribological applications. A succinct comparison of LBAM-fabrication and conventional manufacturing is given. The review provides an insight into the sophisticated application-driven material design for high temperature tribological contacts. The review highlights the major mechanisms behind the improvement in the tribology of the laser-deposits; properties evolving as a consequence of the microstructure, lamellar solid lubricants, sulfides, soft metals, lubricious oxides, and self-lubricating surfaces.